Lipid Peroxidation, Proline Content and Soluble Sugars as indicators of Oxidative Stress Tolerance in Some Advanced Durum Wheat Lines (Triticum durum Desf.). - Oulmi, Abdelmalek; Benkadja, Sarah; Guendouz, Ali; Frih, Benalia; Mehanni, Amor; Selloum, Samir (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2023)
Oxidative stress induced by glyphosate is a complex phenomenon caused by an imbalance between reactive oxygen species (ROS) and antioxidants in plants cells. The present research was carried out at the field crops institute, Agricultural Experimental Station of Setif (ITGC-AES), to assess the response of some durum wheat (Triticum Durum Desf.) lines exposed to oxidative stress induced by glyphosate herbicide. In the heading stage, a solution of 5 Mm of glyphosate  was sprayed on flag leaves, and each measurement was taken 48 hours after the glyphosate application. Lipid peroxidation, free proline and soluble sugars were determined. The results indicated that oxidative stress increased the content of lipid peroxidation, proline, and soluble sugars in flag leaves. Analysis of variance revealed significant differences among the genotypes tested, the increase in the level of lipid peroxidation is much higher in advanced lines G5 and G3, in which lipid peroxidation and membrane damage are greater. Oxidative damage also increased the proline content in lines G3 and G4, and soluble sugars in line G5, which were showing a high tolerance to the oxidative stress induced.